Performance of Modification of a Three Phase Dynamic Voltage Restorer (DVR) for Voltage Quality Improvement in Electrical Distribution System - Omar, Rosli; Sulaiman , Marizan (InTech, 2011)

(untitled)
There is growing concern over power quality of ac supply systems. Power quality can be defined as the ability of utilities to provide electric power without interruption. Various power quality problems can be categorized as voltage sags, swells, harmonics, transients and unbalance are considered are the most common power quality problems in electrical distribution systems (Elandy etl., 2006). These types of disturbances can cause fails in the equipments, raising the possibility of an energy interruption.Voltage swells can be defined as a short duration increase in rms of main source with an increase in voltage ranging from 1.1 p.u up to 1.8 p.u. of nominal voltage source. There are various solutions to these problems